2012
DOI: 10.1111/j.1365-2702.2012.04196.x
|View full text |Cite
|
Sign up to set email alerts
|

People living with serious illness: stories of spirituality

Abstract: Aims and objectives.  To examine stories of spirituality in people living with serious illness. Background.  Although knowledge about the experience of people with various chronic illnesses is growing, there is little known about peoples’ beliefs and perspectives relating to spirituality where there is a diagnosis of a serious chronic and life‐limiting illness. Design of the study.  A social constructionist approach to narrative inquiry was used. Methods.  In‐depth narrative interviews were conducted on one oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
5
24
0
7
Order By: Relevance
“…For example, Walton (2002) illustrated this in a grounded theory study with 11 patients receiving HD treatment in the USA. Similarly, in Canada, patients identified that spirituality is important in their lives and helps them to find meaning in illness, which empowers them to come to terms with their disease (Molzahn et al, 2012). Further evidence from three studies also suggests that the way in which spirituality affects patients" lives is by facilitating coping, which gives patients the ability to adapt and manage their daily lives.…”
Section: Spirituality In the Lives Of Patients With End-stage Renal Dmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, Walton (2002) illustrated this in a grounded theory study with 11 patients receiving HD treatment in the USA. Similarly, in Canada, patients identified that spirituality is important in their lives and helps them to find meaning in illness, which empowers them to come to terms with their disease (Molzahn et al, 2012). Further evidence from three studies also suggests that the way in which spirituality affects patients" lives is by facilitating coping, which gives patients the ability to adapt and manage their daily lives.…”
Section: Spirituality In the Lives Of Patients With End-stage Renal Dmentioning
confidence: 94%
“…Only two studies offered a theoretical justification of their study (Tanyi and Werner, 2003;Molzahn et al, 2012).…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…La narrazione da parte del malato della propria storia e l'ascolto di chi si prende cura di lui, gli permettono di esprimere il proprio disagio e le proprie emozioni, di instaurare una relazione terapeutica efficace, che lo aiuti a prendere le decisioni in modo più consapevole e a esserne più partecipe. Gli studi scientifici presenti in letteratura, svolti nell'ambito della medicina narrativa, sono per lo più di tipo qualitativo e si basano sulla prospettiva costruttivista che parte dal presupposto che persone, gruppi e culture creano e sostengono la loro comprensione e rappresentazione della realtà attraverso la costruzione condivisa di storie (2). Il Nursing Narrativo nasce con gli studi di Paterson e Zderad…”
unclassified